Anthropogenic impact on mangrove sediments triggers differential responses in the heavy metals and antibiotic resistomes of microbial communities. (September 2016) - Cabral, Lucélia; Júnior, Gileno Vieira Lacerda; Pereira de Sousa, Sanderson Tarciso; Dias, Armando Cavalcante Franco; Lira Cadete, Luana; Andreote, Fernando Dini; Hess, Matthias; de Oliveira, Valéria Maia
Abstract: Mangroves are complex and dynamic ecosystems highly dependent on diverse microbial activities. In the last decades, these ecosystems have been exposed to and affected by diverse human activities, such as waste disposal and accidental oil spills. Complex microbial communities inhabiting the soil and sediment of mangroves comprise microorganisms that have developed mechanisms to adapt to organic and inorganic contaminants. The resistance of these microbes to contaminants is an attractive property and also the reason why soil and sediment living microorganisms and their enzymes have been considered promising for environmental detoxification. The aim of the present study was to identify active microbial genes in heavy metals, i.e., Cu, Zn, Cd, Pb and Hg, and antibiotic resistomes of polluted and pristine mangrove sediments through the comparative analysis of metatranscriptome data. The concentration of the heavy metals Zn, Cr, Pb, Cu, Ni, Cd, and Hg and abundance of genes and transcripts involved in resistance to toxic compounds (the cobalt-zinc-cadmium resistance protein complex; the cobalt-zinc-cadmium resistance protein CzcA and the cation efflux system protein CusA ) have been closely associated with sites impacted with petroleum, sludge and other urban waste. The taxonomic profiling of metatranscriptome sequences suggests that members of Gammaproteobacteria and Deltaproteobacteria classes contribute to the detoxification of the polluted soil. Desulfobacterium autotrophicum was the most abundant microorganism in the oil-impacted site and displayed specific functions related to heavy metal resistance, potentially playing a key role in the successful persistence of the microbial community of this site. Highlights: Oil spill contributed to increase heavy metal concentrations in mangrove sediments. Genes related with resistance to heavy metals were upregulated in impacted sites. Gamma and Deltaproteobacteria are crucial in detoxificating the oil spilled mangrove. At the genus level, Geobacter was the most abundant one in Ant Mgv site. Desulfobacterium autotrophicum was the most abundant microorganism in Oil Mgv site. Abstract : Microbial community responses to pollution in contaminated mangroves revealed using metatranscriptomics.